2000
DOI: 10.1002/1097-0215(20000720)89:4<313::aid-ijc1>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic aberrations in the p53 pathway are associated with a high S phase fraction and poor patient survival in b‐cell non‐Hodgkin's lymphoma

Abstract: The implications of aberrations in the p53 pathway for induction of apoptosis and regulation of S phase entry, and for patient survival, were investigated in 83 B-cell NonHodgkin's lymphomas. Eight cases had missense mutations in exons 5, 7, 8 and 9 as revealed by constant denaturant gel electrophoresis and sequencing. Fifteen cases had lost 1 TP53 allele as revealed by fluorescent in situ hybridization and comparative genomic hybridization. Ten cases expressed high levels of p53 as assessed by immunoblotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 18 publications
6
25
0
Order By: Relevance
“…There was also good agreement between the CGH results on 17p and the number of TP53 copies (Table 1; see also Stokke et al, 2000). …”
Section: Verification Of Cgh Results By Direct Measurements Of Specifsupporting
confidence: 58%
See 3 more Smart Citations
“…There was also good agreement between the CGH results on 17p and the number of TP53 copies (Table 1; see also Stokke et al, 2000). …”
Section: Verification Of Cgh Results By Direct Measurements Of Specifsupporting
confidence: 58%
“…Hence, not all four of these aberrations necessarily target genes that are important in the control of cell proliferation. The anti-proliferative activities of wild-type p53 are well documented in the literature (for reviews, see : Sherr, 1996;Levine, 1997), and our previous study showed that a high S phase fraction was characteristic for NHL cases with either mutations in TP53, loss of TP53, or clonal expression of p53 (Stokke et al, 2000).…”
Section: Genomic Imbalances and Prognosis In Non-hodgkin's Lymphoma 1911mentioning
confidence: 68%
See 2 more Smart Citations
“…The expression was measured with antibodies from Oncogene Research Products (San Diego, CA; clone 1801 anti-TP53, clone EA10 anti-CDKN1A), Zymed (San Francisco, CA; clone 33-170 anti-PLK1), DakoCytomation (Glostrup, Denmark; clone 124 anti-BCL2), Pharmingen (now part of Becton Dickinson, San Jose, CA; polyclonal anti-MCL1, clone PMG3-245 anti-RB1), as described previously. 19,20 Lysates of 500,000 cells were loaded per lane. The amount of actin (ACTB; Santa Cruz, Santa Cruz, CA; clone C-2 anti-actin) was determined on the same blots to control for gel loading, cell concentration and protein degradation.…”
Section: Immunoblottingmentioning
confidence: 99%